2003
DOI: 10.1034/j.1600-0420.2003.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception during phacoemulsification cataract surgery under topical and regional anaesthesia

Abstract: ABSTRACT.Purpose: To compare the subjective visual experiences of patients during phacoemulsification and intraocular lens (IOL) implantation using regional and topical anaesthesia. Design: A prospective, cohort, questionnaire-based study. Methods: The study cohort consisted of 247 patients without pre-existing ocular pathology who underwent routine phacoemulsification and IOL implantation. The mean age of the subjects was 75.4 AE 9.4 years and 34.5% of them had a history of cataract surgery. Three different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 11 publications
3
32
2
Order By: Relevance
“…These visual phenomena are mostly independent of comorbidities, sex, age, form of anaesthesia, duration of the operation, mode of cataract surgery, or even sedation. Intraoperative visual illusions can lead to anxiety 2,10,20 or joy. 11,24 This is why patients are counselled about them prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These visual phenomena are mostly independent of comorbidities, sex, age, form of anaesthesia, duration of the operation, mode of cataract surgery, or even sedation. Intraoperative visual illusions can lead to anxiety 2,10,20 or joy. 11,24 This is why patients are counselled about them prior to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that there were no associations between intraoperative visual impression and sex 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The fear is a response to perceived threat which can be minimized by appropriate health education interventions 12 . It is well known that topical anaesthesia preserves optic nerve function 13 and thus patients can experience a vast range of visual stimuli. So, preoperative counselling about possible visual fear could be of value for every patient scheduled to undergo phacoemulsifi cation cataract surgery, in particular, regarding various possible stimuli such as light perception, gush of water and movements e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] We report that flashing lights and floaters are commonly experienced by patients immediately following an IVT injection, and that flashes are experienced by almost two-thirds of patients within the first 2 weeks following the procedure. Preinjection VA, clinical indication for the IVT injection, and the nature of the pharmacological agent injected did not influence the visual experiences of patients, although the authors concede that subgroups analysis was limited because of its small size.…”
Section: Discussionmentioning
confidence: 99%
“…3 Indeed, some authors are even using IVT therapeutic agents for relatively rare disorders, such as central serous chorioretinopathy. 3 Patients' visual perceptions and experiences induced by frequently performed ophthalmic surgical procedures, such as cataract surgery (under topical [10][11][12][13][14][15] and regional anesthesia [11][12][13][14]16,17 ), glaucoma filtration surgery, 18 and vitreoretinal surgery, [19][20][21][22] are well documented. Indeed, the beneficial effect of preoperative counseling with respect to known and anticipated visual experiences during phacoemulsification cataract surgery, under topical anesthesia, in terms of reducing patients' fear, has been described.…”
Section: Introductionmentioning
confidence: 99%